Automotive Hazardous Waste Management in Automotive Shops of Indonesia’s Metropolitan City. Case Study: Bandung City, West Java Province - Widyarsana I Made Wahyu; Mulyadi Aurilia Ayuanda; Tambunan Suci Ameliya (Environmental and Climate Technologies, 2022)
The number of vehicles in Bandung City continues to increase every year in line with the growth of motorized vehicle repair shops, thereby increasing the generation of hazardous waste from automotive shop activities. Based on Indonesia’s Governmental Decree 101 of 2014, vehicle maintenance and repair activities are one of the businesses that produce hazardous waste. This study focused on licensed and unlicensed automotive shops in Bandung City using stratified sampling methods by determining waste generation and composition, evaluating existing management systems, followed by developing management system alternatives. In determining the generation and composition of hazardous waste from automotive shop activities, a sampling of 42 unlicensed automotive shops and 11 unlicensed automotive shops in 3 areas of Bandung City was conducted. Sampling results of hazardous waste generation are 1.83 kg/vehicle/day for motorcycle automotive shops and 6.90 kg/vehicle/day for car automotive shops. The largest composition of hazardous waste produced in licensed shops is used oil with a proportion of 29.60 % and metal scrap component with a proportion of 35.83 % for unlicensed automotive shops. The projection results of hazardous waste generation in 2021 are around 774.26 tonnes/day. If the hazardous waste generated is not properly managed it can pose a risk to human health and the environment. An integrated management system for hazardous waste consists of packaging activity, storage activity, collection, transportation, and recycling activity.